2011
DOI: 10.1111/j.1365-2109.2010.02781.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance of bath sponge (Spongia officinalis Linnaeus, 1759) farmed on suspended ropes in the Dardanelles (Turkey)

Abstract: Commercial bath sponge population in the Mediterranean has been recently reduced due to diseases and the depletion of natural banks. The commercial supply is far below the demand on the last10^15 years. In this study, we aimed to investigate the farming performance of Spongia o⁄cinalis in the Dardanelles. Sponges collected from the Dardanelles cut into pieces of di¡erent weight. They were divided into two groups depending on the wet weight ranging from 50 to150 g (mean weight 102.6 AE 4.81g) and from 160 to 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Duckworth [9] has shown that some sponge species (Latrunculia wellingtonensis and Polymastia croceus) can also recover totally from 90% removal of biomass. As other studies [5,22] have also shown, growth rates of Spongia officinalis between different sized explants are similar. Neopetrosia sp.…”
Section: Recommendations the Precision Of Calculated Volumessupporting
confidence: 79%
See 3 more Smart Citations
“…Duckworth [9] has shown that some sponge species (Latrunculia wellingtonensis and Polymastia croceus) can also recover totally from 90% removal of biomass. As other studies [5,22] have also shown, growth rates of Spongia officinalis between different sized explants are similar. Neopetrosia sp.…”
Section: Recommendations the Precision Of Calculated Volumessupporting
confidence: 79%
“…The higher sedimentation near the bottom leads to the block-up of ostia, causing the sponge to stop feeding and forcing all its energy toward cleaning [23]. For other sponge species like Spongia officinalis no significant differences in growth could be observed for different positions of transplants in the water column [22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although their exact phylogenetic location remains in question, sponges originated near the base of the metazoan phylogeny [ 7 , 8 , 9 , 10 ], which thereby places them at a key transitional position for comparative analyses on the origins of animal body plans [ 11 ], developmental processes and life cycles [ 12 , 13 ], cell/tissue types and multicellularity [ 14 , 15 , 16 , 17 ], and gene families and regulatory networks [ 18 , 19 , 20 , 21 ]. Sponges are also valued as sources of biological compounds and products with pharmaceutical and other practical benefits to humans [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%